2014
DOI: 10.1080/17451000.2014.955802
|View full text |Cite
|
Sign up to set email alerts
|

The importance of vertical habitat gradients on zooplankton distribution in an enclosed marine environment (South Adriatic Sea)

Abstract: The spatio-temporal patterns of a zooplankton community structure in a strongly stratified enclosed marine environment were studied over a one-year period. Copepods were by far the most abundant group, accounting for 69-91% of the total zooplankton, with a numerical dominance of the genus Oithona. Cluster analysis revealed four different groups of samples and a comparison was made of the hydrographical and biological properties of the resulting groups. Water temperature was the main force discriminating the zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…This study confirms their importance, which is even more apparent during the strongest sunlight over the stratified conditions when most of the calanoid species avoid surface layers. Similar results were found in the coastal area of the Mljet lakes, where seasonal studies on the vertical distribution of zooplankton showed that the genus Oithona was numerically dominant during the summer, with O. nana being one of the dominant zooplankton species in the surface layers during the warmest period [53]. As opposed to seasonal changes in vertical positioning, small copepods such as Oithona spp.…”
Section: Discussionsupporting
confidence: 81%
“…This study confirms their importance, which is even more apparent during the strongest sunlight over the stratified conditions when most of the calanoid species avoid surface layers. Similar results were found in the coastal area of the Mljet lakes, where seasonal studies on the vertical distribution of zooplankton showed that the genus Oithona was numerically dominant during the summer, with O. nana being one of the dominant zooplankton species in the surface layers during the warmest period [53]. As opposed to seasonal changes in vertical positioning, small copepods such as Oithona spp.…”
Section: Discussionsupporting
confidence: 81%
“…However, a large variation in both surface (69%) and DCM (52%) RDA models remains unexplained, suggesting that the horizontal patters could not be only explained by bottom-up control and might be highly influenced by other drivers. Studies on vertical zooplankton distribution showed that vertical stratification can hinder the migration of some small zooplankton groups and suggest different grazing pressures above and below the thermocline (Norrbin et al, 1996; Miloslavić et al, 2015). Considering that zooplankton filter feeders and heterotrophic flagellates are the main grazers of the predominant picophytoplankton during summer stratification (Calbet et al, 2008; Guo et al, 2014), further research should focus on whether differences in phytoplankton grazing pressure, associated to the different predators and phytoplankton communities composition, exists between the two water masses.…”
Section: Discussionmentioning
confidence: 99%
“…The components of the phytoplankton community have shown differences in their nutrient uptake efficiency and requirements [54] and in their light quantity and quality adaptation [55]. Studies on vertical zooplankton distribution showed that vertical stratification can hinder the migration of some small zooplankton groups and suggests different grazing pressures above and below the thermocline [56], considering that zooplankton filter feeders and heterotrophic flagellates are the main grazers of the predominant picophytoplankton during the summer stratification [57]. Studies of the phytoplankton community composition between the upper and lower water layers of the thermocline should focus on whether the differences in phytoplankton predation pressure are related to different predators, which was not considered in this study.…”
Section: Effects Of Environmental Factors On Phytoplankton Communitiesmentioning
confidence: 99%